Pemberdayaan Generasi Muda melalui Strategi Pemasaran untuk Meningkatkan Profitabilitas - Achiruddin Siregar; Dian Islamiyati; Hilman Hidayat; Detti Meilandri; Nunung Suryana Jamin (ABDIMAS TERAPAN : Jurnal Pengabdian Kepada Masyarakat Terapan, 2025)
The younger generation is the future of the nation and has great potential to drive social and economic change. This activity was conducted using a participatory approach with training, group discussions, and hands-on practice. Many YWKA Vocational School students still have not implemented marketing strategies in a planned and professional manner and do not understand the concept of profitability. The results of the community service demonstrated an increase in participants' understanding of developing marketing strategies to increase profitability. This community service, in the form of training, is effective in improving the skills of the younger generation.